(untitled) (Research, Society and Development, 2023)
This paper aims to analyze the basis of topical treatment in toxic epidermal necrolysis and Stevens-Johnson syndrome, both severe and rare diseases characterized by necrosis of the epidermis and mucous membranes. Topical treatment is an important option to relieve symptoms and reduce the risk of infections. This includes the use of creams and ointments to promote pain and inflammation relief, and dressings to protect the skin and mucous membranes. To broaden the discussion, aspects such as the characteristics of toxic epidermal necrolysis and Stevens-Johnson syndrome, the types of topical treatment available, the benefits and challenges of topical treatment and the implications for patients’ health will be addressed. In order to reach these topics, articles were collected in the PUBMED, LILACS and SCIELO databases, during the month of July 2023 and an analysis was carried out with firm criteria from the material found to be able to explain the relevant information to the theme. It is concluded in this work that the use of topical methods for the treatment of such syndromes can be of paramount importance, especially when it comes to symptom relief and agility in recovery. However, there is a need for a greater number of randomized and multicenter studies that can enrich research on the topic.